A COMPARATIVE ANALYSIS ON INDONESIAN 2013 AND SLOVENIAN 1999 KINDERGARTEN CURRICULA (Proceedings of the International Conference on Education, 2019)
For about 2 decades, Slovenian preschools have implemented curriculum established in 1999 without any major reform ever since. Meanwhile, Indonesia has changed its school curriculum three times over the same period (2004, 2006, and 2013). The latest change brings with it the reform of Indonesia’s preschool curriculum. Both countries share context of which preschool education is not made compulsory and the prescribed preschool age range is 1 to 6 years old. This research attempted to compare Indonesian 2013 preschool curriculum (K-13) with Slovenian 1999 curriculum in terms of their development and implementation while also trying to uncover the embedded cultural values and influences on both curricula and how they have impacted different shareholders. In doing so, this research was conducted by reviewing the collated official curriculum documents published by education ministry of the two countries while analysing facts, statistics and issues emerged from related studies and articles. Similarities were found in terms of them functioning as the foundation for the education system, optimised parents’ roles, the flexibility of implementation, and their philosophical bases. Slight to significant differences were found in the included parties within the designing processes, the documented and elaborated goals, the privileged groups, and their effects on teachers, staff and school institutions in the implementation basis. The findings suggest that Indonesian curriculum needs to be made more practical instead of being too philosophical while gradual and continuous evaluation in necessary aspects is more recommended than total reforms which tend to result in longer adaptation and transition process.
Keywords: Indonesian preschool; Kindergarten Curriculum; Slovenian Preschhol